Global and Brazilian Carbon Response to El Niño Modoki 2011–2010. Issue 10 (22nd October 2017) - Bowman, K. W.; Liu, J.; Bloom, A. A.; Parazoo, N. C.; Lee, M.; Jiang, Z.; Menemenlis, D.; Gierach, M. M.; Collatz, G. J.; Gurney, K. R.; Wunch, D.
Abstract : The El Niño Modoki in 2010 led to historic droughts in Brazil. In order to understand its impact on carbon cycle variability, we derive the 2011–2010 annual carbon flux change ( δ F ↑ ) globally and specifically to Brazil using the NASA Carbon Monitoring System Flux (CMS‐Flux) framework. Satellite observations of CO2, CO, and solar‐induced fluorescence (SIF) are ingested into a 4D‐variational assimilation system driven by carbon cycle models to infer spatially resolved carbon fluxes including net ecosystem production, biomass burning, and gross primary productivity (GPP). The global 2011–2010 net carbon flux change was estimated to be δ F ↑ =−1.60 PgC, while the Brazilian carbon flux change was −0.24 ± 0.11 PgC. This estimate is broadly within the uncertainty of previous aircraft‐based estimates restricted to the Amazon basin. The 2011–2010 biomass burning change in Brazil was −0.24 ± 0.036 PgC, which implies a near‐zero 2011–2010 change of the net ecosystem production (NEP): The near‐zero NEP change is the result of quantitatively comparable increases GPP (0.31 ± 0.20 PgC) and respiration in 2011. Comparisons between Brazilian and global component carbon flux changes reveal complex interactions between the processes controlling annual land‐atmosphere CO2 exchanges. These results show the potential of multiple satellite observations to help quantify and spatially resolve the response of productivity and respiration fluxes to climate variability. Plain Language Summary: We quantify the global and Brazilian carbon response to 2010 El Niño using the NASA Carbon Monitoring System Flux (CMS‐Flux) framework. Satellite observations of CO2, CO, and solar‐induced fluorescence (SIF) are ingested into a 4D‐variational assimilation system driven by carbon cycle models to infer spatially resolved carbon fluxes including net ecosystem exchange, biomass burning, and gross primary productivity (GPP). We show that CO2 biomass burning from Brazil was both the dominant driver of net carbon exchange in Brazil and the dominant contributor to the global biomass burning from 2011–2010. Key Points: Global and Brazilian annual net, fire, and GPP CO2 flux for 2010–2011 was estimated with assimilated satellite data Fire from Brazil (−0.24 ± 0.11 Pg C) dominated the global biomass burning 2011–2010 carbon flux change The positive Brazilian GPP change was symmetrically balanced by total ecosystem respiration